2017
DOI: 10.1055/s-0037-1604053
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapeutic Strategies in the Treatment of Hemophilia A

Abstract: The development of therapeutic strategies for the treatment of hemophilia A has been a long-lasting issue since the initial identification of the disease in the early 19th century and has involved several major steps to reach contemporary treatment. The current replacement therapy involving intravenous infusion of plasmatic or recombinant factor VIII (FVIII) has been efficient to control bleeding episodes of patients with hemophilia A. Nonetheless, replacement therapy requires frequent infusions to maintain va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The therapeutic armamentarium for hemophilia is rapidly expanding (18,19,31). However, the clinical development of several new products has been marred by unanticipated thrombotic complications and subject deaths (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic armamentarium for hemophilia is rapidly expanding (18,19,31). However, the clinical development of several new products has been marred by unanticipated thrombotic complications and subject deaths (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The conjugated polypeptides can be subcutaneously administered and target hepatocytes through uptake by asialo‐glycoprotein receptors. An antithrombin siRNA agent was developed (ALN‐AT3; fitusiran) to turn off the hepatic expression of antithrombin mRNA 77,78 . An animal model study with subcutaneous fitusiran administration demonstrated dose‐dependent, potent, and durable reduction of antithrombin levels, restoring haemostasis and improving coagulant potential 7 …”
Section: Rebalancing Therapymentioning
confidence: 99%
“…An antithrombin siRNA agent was developed (ALN-AT3; fitusiran) to turn off the hepatic expression of antithrombin mRNA. 77,78 An animal model study with subcutaneous fitusiran administration demonstrated dose-dependent, potent, and durable reduction of antithrombin levels, restoring haemostasis and improving coagulant potential. 7 Anti-TFPI mAb TFPI is a Kunitz-type (K) proteinase inhibitor that functions essentially in governing TF-associated procoagulant responses.…”
Section: Antithrombin-targetingmentioning
confidence: 99%
“…Fitusiran is an antithrombin RNA interference molecule (ALN-AT3; fitusiran, (Alnylam/Sanofi) which decreases antithrombin (AT) messenger RNA expression in the liver. 90 , 91 AT is a natural anticoagulant which inactivates FXa and thrombin. Deficiency of AT results in a prothrombotic state due to excess TG.…”
Section: Non-replacement Therapiesmentioning
confidence: 99%